Bentuk Pertunjukan Drama Tari Bejoraq - Ashwan Kailani; Hary Murcahyanto; Mariadah Mariadah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aimed to to describe the element of performance form and the meaning of the motion of the drama